2019
DOI: 10.1111/jph.12818
|View full text |Cite
|
Sign up to set email alerts
|

In vitro antimicrobial effect of metallic nanoparticles on phytopathogenic strains of crop plants

Abstract: In this research, the in vitro antimicrobial effect of zinc oxide (ZnO), copper oxide (CuO) and iron oxide (Fe2O3) nanoparticles (NPs)—with average sizes of 20, 46 and 30 nm, respectively—on the root rot disease caused by the fungus Fusarium oxysporum and on blight disease caused by the fungus Alternaria solani were studied. Also, bacterial diseases caused by Clavibacter michiganensis and Pseudomonas syringae that infects a wide range of plant species were assessed. Different concentrations of NPs (0, 100, 250… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…Plant extract-mediated CuO NPs have minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) at 25, 100, and 1000 mg/ml. Moreover, the fungal filtrate-synthesized CuO NPs were found to be efficient at 25–250 ppm dose ( Giannousi et al, 2013 ; Vera-Reyes et al, 2019 ). Thus, all these studies have showed that lower doses of CuO NPs (25–1,000 ppm) are sufficient to kill the pathogen, which are supporting the antifungal activity of our M-CuO NPs (25–200 ppm).…”
Section: Resultsmentioning
confidence: 99%
“…Plant extract-mediated CuO NPs have minimum inhibitory concentration (MIC) and minimum fungicidal concentration (MFC) at 25, 100, and 1000 mg/ml. Moreover, the fungal filtrate-synthesized CuO NPs were found to be efficient at 25–250 ppm dose ( Giannousi et al, 2013 ; Vera-Reyes et al, 2019 ). Thus, all these studies have showed that lower doses of CuO NPs (25–1,000 ppm) are sufficient to kill the pathogen, which are supporting the antifungal activity of our M-CuO NPs (25–200 ppm).…”
Section: Resultsmentioning
confidence: 99%
“…Root damping-off diseases are widely disturbed all over the world and are recognized as a serious problem to soybean cultivators, as they significantly decrease the bean yield. Several control measures of the disease are available, including fungicidal control, enhancement of genetic resistance, which may lead to deteriorating human health [5,20]. In Egypt, there is no active control method to reduce damping-off of many crops and vegetable plants caused by P. aphanidermatum although, that pathogenic is widely distributed throughout the country [17,18,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…Root rot diseases of G. max are widespread in the world and are usually recognized as the main constraint to decrease both yield and quality [2,3]. Pythium as a causal agent for Glycine max root rots has been mentioned as being the main reason leading to soybean yield losses in numerous countries [4,5]. Pythium aphanidermatum has been reported as the species most frequently causing root rot diseases for the greatest variety of crops [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Research works have also showed that other factors, such as the concentration of nanoparticles used to inhibit the growth of phytopathogenic fungi and characteristics of fungal species, influence the antifungal activity [87]. In general, the inhibition of phytopathogenic fungi tends to increase under in vitro evaluations when the concentration of the ZnO-NPs increases [46,[48][49][50][51]53,54,60,[63][64][65][66][67][69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84][85]. Interestingly, low concentrations (100-1000 ppm) of ZnO-NPs have shown excellent results for controlling phytopathogenic fungi.…”
Section: Antifungal Properties Of Mono-metal Oxide Nanoparticles 21 Z...mentioning
confidence: 99%